A Selective Electrochemical Sensor for Bisphenol A Detection Based on Cadmium (II) (bromophenyl)porphyrin and Gold Nanoparticles - Fatma Rejab; Nour Elhouda Dardouri; Ahlem Rouis; Mosaab Echabaane; Habib Nasri; Boris Lakard; Hamdi Ben Halima; Nicole Jaffrezic-Renault (Micromachines)
Bisphenol A (BPA) is a commonly synthetic chemical mainly used in producing plastic items. It is an endocrine-disrupting compound that causes irreversible health and environmental damage. Developing a simple method for BPA effective quantitative monitoring is emergently necessary. Herein, a novel electrochemical sensor for BPA detection based on [(5,10,15,20-tetrakis(p-bromophenyl) porphyrinato] cadmium (II) [(CdTBrPP)] and gold nanoparticle (AuNPs)-modified screen-printed carbon electrode (SPCE) was elaborated. CdTBrPP was synthesized and then characterized with Ultraviolet–Visible Spectroscopy (UV/vis), Infrared Spectroscopy (IR), and Proton Nuclear Magnetic Resonance Spectroscopy (1H NMR) to confirm its successful synthesis. After drop-coating AuNPs and CdTBrPP on the SPCE, the sensor performance was evaluated using square wave voltammetry (SWV), a linear response in a concentration range from 10−11 M to 10−2 M, with a low detection limit (LOD) of 9.5 pM. The CdTBrPP/AuNPs/SPCE sensor demonstrates a high selectivity and reproducibility, making it a promising candidate for developing a low-cost water-monitoring system for detecting BPA. Additionally, the proposed sensor effectively detected BPA in both tap and mineral water samples.